Traffic Performance Optimization at Batanghari Intersection Using Microsimulation - Kenny Ghalib; Yossyafra Yossyafra; Purnawan Purnawan (Universitas Tribhuwana Tunggadewi Malang, 2024)
The Batanghari 1 Bridge serves as a vital link connecting Jambi City and Muaro Jambi Regency. Currently, the traffic density at the Batanghari intersection is notably high, particularly during peak hours, resulting in frequent traffic jams. To address this issue, the Perencanaan dan Pengawasan Jalan Nasional (P2JN) and Planning Consultants executed a Detailed Engineering Design (DED) Planning for the Duplication of the Batanghari 1 Bridge in 2021. The Duplication DED transformed the original intersection into a combination of an intersection and a U-turn. However, a notable challenge emerged during rush hours, especially for Jalan KH.A. Majid, where a U-turn is essential to cross the Batanghari Bridge. In this study, a traffic microsimulation was initiated at the Batanghari intersection. Using PTV Vissim software, microsimulations were conducted under three scenarios: Existing Condition, Detailed Engineering Design (DED), and an Alternative scenario, which involved incorporating a Flyover for KH.A. Majid Road towards Batanghari Bridge. Furthermore, traffic microsimulations were conducted to anticipate conditions over the next two decades. The analysis involved microsimulation using Vissim software, encompassing calibration, trial and error validation of the intersection model considering driver behavior, and GEH tests on traffic volume. The microsimulation results at the Batanghari intersection revealed that the alternative model effectively reduced queues, minimized delay times, and improved overall travel time compared to the proposed model.